Here's the question you clicked on:
sara1234
HELPPP
Verify each trigonometric equation by substituting identities to match the right hand side of the equation to the left hand side of the equation.
2. (sin x)(tan x cos x – cot x cos x) = 1 – 2 cos^(2)x
sin *tanx*cosx-sinx *cotx*cosx |dw:1353183388405:dw|
sin^2x-sinx now further solve u will get right hand side
sara did u understand my solution
sorry i done a mistake
here is wright answer tanx = (sinx/cosx) cotx = (cosx/sinx) sinx cosx (tanx - cot x) = sinx cosx (sinx/cosx - cosx/sinx) Cross multiply the equation in the braket and make the in same denomenator. =sin x cos x ((sin^2x - cos^2x)/(cosx sinx)) = sin^2x - cos^2x Replace sin^2 by 1 - cos^2x = 1 - cos^2x - cos^2x = 1 - 2cos^2x